How to do nothing : resisting the attention economy - Odell, Jenny (Multimedia artist) (Brooklyn, NY : Melville House, 2019)
"A galvanizing critique of the forces vying for our attention--and our personal information--that redefines what we think of as productivity, reconnects us with the environment, and reveals all that we've been too distracted to see about ourselves and our world. Nothing is harder to do these days than nothing. But in a world where our value is determined by our 24/7 data productivity ... doing nothing may be our most important form of resistance. So argues artist and critic Jenny Odell, who sees our attention as the most precious--and overdrawn--resource we have. Once we can start paying a new kind of attention, she writes, we can undertake bolder forms of political action, reimagine our role in the environment, and arrive at more meaningful understandings of happiness and progress. Far from a simple anti-technology screed or back-to-nature meditation, How to Do Nothing is an action plan for thinking outside of the narratives of efficiency and techno-determinism. Provocative, timely, and utterly persuasive, this book is a four-course meal in the age of Soylent."
The case for nothing -- The impossibility of retreat -- Anatomy of a refusal -- Exercises in attention -- Ecology of strangers -- Restoring the grounds for thought -- Conclusion : Manifest dismantling.
Includes bibliographical references (pages 207-218) and index.
Keywords: Information technology -- Social aspects; Reflection (Philosophy); Attention -- Philosophy; Work -- Philosophy; Arts -- Philosophy